2021
DOI: 10.1159/000517555
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Cause Sex-Specific Vascular Changes via Cofilin-Extracellular Signal-Regulated Kinase Signaling: Female Mice Present Higher Risk of Developing Morphine-Induced Vascular Dysfunction than Male Mice

Abstract: Recent studies have shown that chronic use of prescription or illicit opioids leads to an increased risk of cardiovascular events and pulmonary arterial hypertension. Indices of vascular age and arterial stiffness are also shown to be increased in opioid-dependent patients, with the effects being more marked in women. There are currently no studies investigating sex-specific vascular dysfunction in opioid use, and the mechanisms leading to opioid-induced vascular damage remain unknown. We hypothesized that exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…Similarly, Cheon et al reported that female mice showed a greater risk of morphine-induced vascular dysfunction, increased arterial stiffness, and resistance via the cofilin-ERK signaling pathway, suggesting that impaired endothelial function may contribute to the high blood pressure in female rats along with sympathetic activation. 73 Taken together, the results from our study provide evidence that prenatal exposure to exogenous opioids may alter the programming and sensitivity of the vasculature to Ang II in a sex-specific manner. Although the circulating levels of RAS components were similar between vehicle and morphine-exposed rats, because of the discrepancy between in vivo and ex vivo responses, differences in RAS peptides at the central nervous system level cannot be ruled out.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, Cheon et al reported that female mice showed a greater risk of morphine-induced vascular dysfunction, increased arterial stiffness, and resistance via the cofilin-ERK signaling pathway, suggesting that impaired endothelial function may contribute to the high blood pressure in female rats along with sympathetic activation. 73 Taken together, the results from our study provide evidence that prenatal exposure to exogenous opioids may alter the programming and sensitivity of the vasculature to Ang II in a sex-specific manner. Although the circulating levels of RAS components were similar between vehicle and morphine-exposed rats, because of the discrepancy between in vivo and ex vivo responses, differences in RAS peptides at the central nervous system level cannot be ruled out.…”
Section: Discussionsupporting
confidence: 62%